INTERNALIZATION OF FISHERMEN'S ZAKAT TOWARDS THE BENEFITS OF ECONOMIC LIFE COASTAL COMMUNITIES - Yaqin, Ainol (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
The aim of this research is to rejuvenate the internalization of fishermen's zakat (muzakki) distributed to fishermen (mustahik) as an economic contribution to their lives. It is currently very urgent to develop the concept of marine and fisheries zakat, the irony is that the economic problems of coastal communities, including poverty, unemployment, inequality, violence, lack of access to education and health, are concentrated in coastal communities. Zakat as a philanthropic instrument is able to solve the economic problems of coastal communities, the source of the concept of zakat as a divine flow should be internalized in reality. Properly targeted placement of marine and fisheries zakat will reduce the economically problematic population of fishermen. The economic prospect of zakat is to empower and raise the economic level of mustad'ifin. Maritime zakat attention at this time must be aimed at coastal areas, because they are the ones who contribute to developing the maritime business economy and are in direct contact with nature. This research method is to use a qualitative library research model approach. This research methodology is very simple and easy, starting with looking for zakat references, Islamic literacy as secondary data and comparison of reputable journals. The concept of zakat for fishermen is the authority of fiqh and ulama (Muslim scholars). Fishermen must be placed in a high position on the religious side, as are muzakki at the level of trade, agriculture, animal husbandry and others. Fishermen and the sea must be formulated into Islamic law so that fishermen continue to pursue their world and young people aspire to become fishermen. The natural wealth of the sea is not comparable to the economic problems of fishermen. The right solution is to rejuvenate fishermen's zakat for the benefit of coastal communities.